Determinants of fertility desire among married or cohabiting individuals in Rakai, Uganda: a cross-sectional study - Matovu, Joseph K. B.; Makumbi, Fredrick; Wanyenze, Rhoda K.; Serwadda, David (Reproductive health, 2017)
Recent trends in fertility rates indicate declines in total fertility rate (TFR) in some sub-Saharan African countries. However, countries such as Uganda continue to have a persistently high TFR partly attributed to strong preferences for large family sizes. We explored the factors that influence fertility desire among married or cohabiting individuals in Rakai, a rural district in southwestern Uganda. Methods This cross-sectional study of fertility desire (desire to have another child) was nested in a cluster-randomized demand-creation intervention trial for the promotion of couples’ HIV counseling and testing uptake among married or cohabiting individuals that was conducted in Rakai district between March 1 and April 30, 2015. A total of 1490 married or cohabiting individuals, resident in three study regions with differing background HIV prevalence, were enrolled into the study. Data were collected on socio-demographic, behavioral and fertility-related characteristics. We used a modified Poisson regression model to generate prevalence ratio (PR) as a measure of association for factors that were independently associated with fertility desire. We adjusted for clustering at community level and used STATA version 14.0 for all analyses. Results Overall, fertility desire was high (63.1%, n = 940); higher in men (69.9%, n = 489) than women (57.1%, n = 451). More than three-quarters (78.8%, n = 1174) had 3+ biological children while slightly more than two-thirds (68.5%, n = 1020) reported an ideal family size of 5+ children. Only 30% (n = 452) reported that they had attained their desired family size. After adjusting for potential and suspected confounders, the factors that were negatively associated with fertility desire were: age 30–39 (adjusted prevalence ratio [aPR] = 0.82, 95% CI: 0.78, 0.86) and 40+ years (aPR = 0.65, 95% CI: 0.60, 0.71); having six or more biological children (aPR = 0.88, 95% CI: 0.80, 0.97); being HIV-positive (aPR = 0.86, 95% CI: 0.78, 0.95) and ever use of any family planning methods (aPR = 0.93, 95% CI: 0.87, 0.99). Being male (aPR = 1.19, 95% CI: 1.07, 1.33); having primary education (aPR = 1.21, 95% CI: 1.01, 1.44) and having not yet attained the desired family size (aPR = 4.34, 95% CI: 3.50, 5.38) were positively associated with fertility desire. Conclusion Having not yet attained one’s desired family size, being male and having primary education were positively associated with fertility desire in this population. Targeting individuals who have not yet attained their desired family size, men and less educated individuals with fertility regulation interventions may help to reduce fertility desire in this population.